1990
DOI: 10.1007/bf03174850
|View full text |Cite
|
Sign up to set email alerts
|

Petrophysical characteristics of holocene beachrock

Abstract: Beachrocks from the Bahamas, Red Sea, Persian Gulf, Mediterranean, southern Caribbean, and Great Barrier Reef (Australia) were classified into six groups on the basis of lithologic and petrophysical characteristics, as follows: Group A--oolitic grainstone, Group B--skeletal grainstone, Group C--packstone, Group D--dolostone, Group E--terrigenous beach-rock, and Group F--Halimeda grainstone. Because for most purposes, groups Band F can be merged, this study recognizes five petrofacies among beachrocks.Cementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Examples havebeencitedbySugden (1962), DeGroot(1969), Shinn (1969), Taylor and Illing (1969), Evamy (1973), Lareau and Purser (1973), Khalaf (1988) and Guo and Friedman (1990). Recently, beachrocks occurrence was reported on Kuwait by El-Sayed (1996) and on the UAB by Kendall et al (1994) andWhittleet al (1998.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Examples havebeencitedbySugden (1962), DeGroot(1969), Shinn (1969), Taylor and Illing (1969), Evamy (1973), Lareau and Purser (1973), Khalaf (1988) and Guo and Friedman (1990). Recently, beachrocks occurrence was reported on Kuwait by El-Sayed (1996) and on the UAB by Kendall et al (1994) andWhittleet al (1998.…”
Section: Introductionmentioning
confidence: 97%
“…Many of studies of beachrocks have reported on the mechanisms of beach cementation and their petrophysical characteristics, including thoseof Ginsburg (1953), Friedman (1964), Gavish and Friedman (1969), Taylor and llling (1969), and Guo and Friedman (1990). This paper Carbonates and Evaporites, v. 14,no.…”
Section: Introductionmentioning
confidence: 99%
“…Of these parameters, porosity, recovery efficiency, median throat size, normalized throat size, and the forms of capillary pressure curves are regarded as the most significant (Wardlaw, 1976;Wardlaw and Mckellar, 1981;Jennings, 1987;Amthor et al, 1988;Kopaska-Merkel and Amthor, 1988;Wardlaw et al, 1988;Ghosh and Friedman, 1989;Kopaska-Merkel and Friedman, 1989;Friedman et al, 1990;Guo and Friedman, 1990). B Porosity The porosity of modern reef rock ranges from less than 1% to almost 50% (Table 2).…”
Section: Petrophysics Of Modern Reef Rockmentioning
confidence: 99%
“…The modern version of milk alkali syndrome affects a different patient population and has a different etiologic basis than was characterized in the original descriptions of the syndrome (4) in contact with carbon dioxide (5) . These other uses include oil refining, making synthetic rubber, and explosives (5) .…”
Section: Introductionmentioning
confidence: 99%